Culture and perception of leadership: Ideal leader in the country of origin and the country of residence - case of Germany. Study report (part two) = Kultura a percepcja przywództwa. Przywódca idealny w kraju pochodzenia i w kraju wyjazdu na przykładzie Niemiec. Raport z badań (część druga) - Witkowski, Stanisław; Grotthus, Magdalena (Zielona Góra: Faculty of Economics and Management Press)
The present paper is a supplement to the earlier report (Witkowski, Grotthus, 2011) from the intercultural research concerned with an ideal leader prototype from an immigrant?s perspective. In the present part, the authors focus consecutively on four groups of foreigners (Poland, Eastern Europe, Latin Europe, Latin America) working in Germany. Comparison of outstanding leader prototypes in the country of origin and Germany yielded significant differences in all groups.
Keywords: przywódca; lider; kultura przywództwa; percepcja przywództwa; emigrant; leadership; culture of leadership; immigrant; perception of leadership